Conceptualizing transformative tourism experiences: An integrative framework for entrepreneurs - Atari, J.; Dias, Á. (European Journal of Tourism Research, 2025)
The study explores the factors that influence the design of transformative tourism experiences and the co-creation of value, from the perspective of tourism entrepreneurs. The research proposes a conceptual model that integrates various resources and triggers that contribute to the design of transformative experiences and the co-creation of value, ultimately leading to customer self-change. The model highlights the importance of considering both transformative experience design and value co-creation as distinct yet overlapping concepts, each requiring specific resources and attention. The study emphasizes the role of entrepreneurs in facilitating transformative experiences through activities, sensory design, human capital, social capital, and marketing capabilities. The findings offer valuable insights for tourism entrepreneurs and policymakers seeking to develop and promote transformative tourism experiences that foster meaningful and lasting change in travellers.